2021
DOI: 10.1108/oir-01-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning acceptance and use in higher education during social distancing circumstances: an expansion and customization of UTAUT2

Abstract: PurposeThis paper investigates if the existing degree of students' acceptance and use of mobile or m-learning may face the online shift determined by SARS-CoV-2. Based on the extended unified theory of acceptance and use of technology (UTAUT2), a new comprehensive model, SD-UTAUT (social distancing-UTAUT), is developed to better understand relationships between the original constructs, plus personal innovativeness (PI) and information quality (IQ). It identifies the key factors affecting behavioral intention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 48 publications
4
59
0
2
Order By: Relevance
“…These assumptions hold true especially in light of the rapid, erratic, and sudden outbreak of COVID-19. While the role of technology in supporting people in ordinary conditions is widely recognized, it is unclear the extent to which technology is capable to respond to their needs in unusual circumstances and extreme conditions such as COVID-19 [8].…”
Section: Introductionmentioning
confidence: 99%
“…These assumptions hold true especially in light of the rapid, erratic, and sudden outbreak of COVID-19. While the role of technology in supporting people in ordinary conditions is widely recognized, it is unclear the extent to which technology is capable to respond to their needs in unusual circumstances and extreme conditions such as COVID-19 [8].…”
Section: Introductionmentioning
confidence: 99%
“…This complicates the process of conducting a consistent analysis of instructor adoption. Modified versions of UTAUT2 have often eliminated moderating factors rendering a transparent comparison of studies unlikely (Gunasinghe et al , 2019; Mittal et al , 2021; Sitar-Taut and Mican, 2021), similar to studies using the related TAM model (Gibson et al , 2008; Rienties et al , 2016; Teo, 2010; Yuen and Ma, 2002).…”
Section: Suggestions For Further Research and Conclusionmentioning
confidence: 99%
“…Crompton and Burke (2018) found that 74% were undergraduate students and 54% took place in a formal education context. Thus, scholars have recently highlighted the importance of M-learning acceptance and use of applications in the context of higher education (Sitar-Taut and Mican, 2021;Yip et al, 2021). Prior studies argued that M-learning offers a number of benefits, such as enhancing learners' skills, providing opportunities to learn new things, enriching the learning experience, facilitating information sharing and communication, offering study helps to learners enhance confidence and learners' achievements and reducing cost (Crompton and Burke, 2018;Gureyev et al, 2020;Hamidi and Chavoshi, 2018;Reychav et al, 2015;Tan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Crompton and Burke (2018) found that 74% were undergraduate students and 54% took place in a formal education context. Thus, scholars have recently highlighted the importance of M-learning acceptance and use of applications in the context of higher education (Sitar-Taut and Mican, 2021; Yip et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%